Gestión de inversiones y la rentabilidad de las empresas que fabrican productos derivados del papel - Barreiro Alvarez, Andrea Michelle (2023)
The main objective of this study called "Investment Management and the Profitability of companies that manufacture paper products", is to analyze how investment management affects the performance of companies of paper products. Currently, companies in this sector choose not to invest in the stock market, because our country lacks financial culture, this causes companies to not ensure their growth and increase their performance exponentially, so it is important that companies in this sector identify their potential investments and possible business opportunities. When it comes to investing in the stock market, today's companies do not try to ensure growth, but investments are based on experience, which makes the investment not always correct and often leads to losses for the company. This document contains the development of each of the specific objectives that consisted of the theoretical support of the research, the application of qualitative, quantitative methodology, through methodological triangulation, analysis of results and financial statements, preparation of technical report and the formulation of conclusions and recommendations that solve the objectives proposed in the technical report.